Buen vivir y pueblos indígenas en Colombia - Rosa, Oscar David Montero de la (Revista de Estudos em Relações Interétnicas | Interethnica, 2017)
Resumen A partir de la Constitución Política de 1991, Colombia se reconoce como un país multiétnico y pluricultural. Los 102 Pueblos Indígenas existentes en el país tienen como principios de lucha el Territorio, la Cultura, la Autonomía y la Unidad. Hoy el movimiento indígena colombiano, es un referente consolidado, a pesar del exterminio físico y cultural. Actualmente 36 pueblos están en riesgo de extinción, a raíz de las políticas estatales, el conflicto armado interno y el desarrollo occidental.Â  El movimiento indígena platea alternativas propias de acuerdo a sus usos y costumbres para una sociedad diversa e intercultural para el Buen Vivir de la humanidad. Este trabajo tiene como objetivo presentar las dinámicas sociales, culturales y políticas de los Pueblos Indígenas, como sujetos políticos colectivos.Â  Palabras claves: Buen Vivir, territorios indígenas, madre tierra y cosmovisión. Â  Abstract Colombia is a multiethnic and pluri-cultural country according to article 7 of the Political Constitution of Colombia. Achievement that was given by the resistance and cohesion of the indigenous movement, despite being only 3.28% of the Colombian population, where there are 102 indigenous peoples, which has as principles of struggle: territory, culture, autonomy and unity. Today the Colombian indigenous movement is a reference for the social movements of the country and the Abya Yala movement of peace that raises own alternatives according to their uses and customs for a diverse and intercultural society for the good living of humanity. Despite the fact that extermination in which it lives both physically and culturally, since there are 36 peoples in extinction, as a result of the state policies, the internal armed conflict and the development proposal posed by the West. This research project aims to explain the social, cultural and political dynamics that indigenous peoples have as collective political subjects with respect to the territory and the Good Living that is lived in it. Re meaning the traditions, the uses and imaginaries that we have to maintain our principles of struggle and identity, affected by current problems outside our peoples. Keywords: Good Living, indigenous territories, development, Mother Earth, cosmology, cosmogony, interculturality.